Physical exercise can enhance meaning in life of college students: the chain mediating role of self-efficacy and life satisfaction - Guo, Yuncheng; Qin, Keyi; Yu, Yida; Wang, Lixia; Xu, Fanglei; Zheng, Qishan; Hou, Xinyu; Zhang, Yan; Hu, Biying; Hu, Qingping; Gu, Chuanhua; Zheng, Jianhong (Frontiers in Psychology, 2024)
Meaning in life refers to an individual’s capacity to understand and grasp the meaning of their own existence, as well as being aware of the goals, tasks, or missions in their personal life. Previous studies have found that college students lack meaning in life, but physical exercise can enhance it. In this study, 3,196 college students completed self-report questionnaires to assess self-efficacy, life satisfaction, physical exercise, and meaning in life. The results revealed that the physical exercise not only influenced an individual’s perceived meaning in life directly, but also influenced it through self-efficacy. Furthermore, it confirmed the chain mediating role of self-efficacy and life satisfaction, whereby engaging in physical exercise can ultimately impact meaning in life through self-efficacy and life satisfaction. This discovery can help educators create interventions to improve college students’ physical exercise engagement and overall life satisfaction.